2021
DOI: 10.1038/s41374-021-00642-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of the dietary flavonoid fisetin in suppressing rRNA biogenesis

Abstract: The nucleolus of a cell is a critical cellular compartment that is responsible for ribosome biogenesis and plays a central role in tumor progression. Fisetin, a nutraceutical, is a naturally occurring flavonol from the flavonoid group of polyphenols that has anti-cancer effects. Fisetin negatively impacts several signaling pathways that support tumor progression. However, effect of fisetin on the nucleolus and its functions were unknown. We observed that fisetin is able to physically enter the nucleolus. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…It also exhibits affinity and specificity for significant cell cycle regulatory molecules, such as CDK6. Upon co-crystallization with CDK6, it was found that fisetin successfully inhibited kinase activity, which is one of the major drivers in cancer [ 40 , 41 ]. Thus, it regulates cell survival and growth as well as cell proliferation by controlling various signaling mechanisms [ 42 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…It also exhibits affinity and specificity for significant cell cycle regulatory molecules, such as CDK6. Upon co-crystallization with CDK6, it was found that fisetin successfully inhibited kinase activity, which is one of the major drivers in cancer [ 40 , 41 ]. Thus, it regulates cell survival and growth as well as cell proliferation by controlling various signaling mechanisms [ 42 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Fisetin inhibits cell proliferation by targeting the ERK-dependent signaling pathway in astrocytes and gastric cancer [ 14 , 69 ]. In breast cancer cells, fisetin reduces the expression of MMP-9 by inhibiting PKCα/ROS/ERK1/2 and p38 MAPK activation, thereby leading to a decrease in cell migration [ 70 ]. Furthermore, fisetin has been found to regulate MAPK signaling to inhibit cell proliferation and induce apoptosis in acute promyelocytic leukemia cells [ 71 ].…”
Section: Signaling Pathways Of Fisetin (Fig 2 )mentioning
confidence: 99%
“…Pharmacokinetics and metabolism studies of FIS in vivo have elucidated that geraldol (3,4 ,7-trihydroxy-3 -methoxyflavone) is its active, methoxylated metabolite. It has been shown that it is the only one to locate in the nucleolus, and other structurally similar flavonols do not have such ability [18]. FIS is very hydrophobic in nature, resulting in limited water solubility (<0.8 mg/mL).…”
Section: Flavonolsmentioning
confidence: 99%
“…FIS increases the levels of activated caspase-8 [84], -9 and -3 [83] and induces the expression of TNFR-1 and TNFR-2 death receptors, but has no effect on DR-3, -4 and -5, which in association with the protein Bcl-2 and Bax indicate concomitant activation of both external and internal apoptotic pathways [84]. [18] HCC1806, HCC70, HCC1937, BT-549, 20…”
Section: Activity Toward Melanoma Cancer Cellsmentioning
confidence: 99%